Hello beautiful ebook - Napolitano, Ann (2023)
NEW YORK TIMES BESTSELLER • OPRAH’S BOOK CLUB PICK • MORE THAN ONE MILLION COPIES SOLD! From the author of Dear Edward comes a “powerfully affecting” ( People ) family story that asks: Can love make a broken person whole? “Another tender tearjerker . . . Napolitano chronicles life’s highs and lows with aching precision.”— The Washington Post ONE OF THE CHICAGO PUBLIC LIBRARY’S TEN BEST BOOKS OF THE YEAR  A BEST BOOK OF THE YEAR: The New York Times Book Review, NPR, The Washington Post, Time, Vogue, Glamour, Harper’s Bazaar, New York Post, She Reads, Bookreporter William Waters grew up in a house silenced by tragedy, where his parents could hardly bear to look at him, much less love him—so when he meets the spirited and ambitious Julia Padavano in his freshman year of college, it’s as if the world has lit up around him. With Julia comes her family, as she and her three sisters are inseparable: Sylvie, the family’s dreamer, is happiest with her nose in a book; Cecelia is a free-spirited artist; and Emeline patiently takes care of them all. With the Padavanos, William experiences a newfound contentment; every moment in their house is filled with loving chaos. But then darkness from William’s past surfaces, jeopardizing not only Julia’s carefully orchestrated plans for their future, but the sisters’ unshakeable devotion to one another. The result is a catastrophic family rift that changes their lives for generations. Will the loyalty that once rooted them be strong enough to draw them back together when it matters most? An exquisite homage to Louisa May Alcott’s timeless classic, Little Women , Hello Beautiful is a profoundly moving portrait of what is possible when we choose to love someone not in spite of who they are, but because of it.